Produktivitas Kerja Karyawan Jasa Pengiriman Barang Dengan Kepuasan Kerja Sebagai Intervening Variabel - I Gede Pasek Oka Mahendra; Luh Putu Mahyuni (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2023)
The rapid development of the freight forwarding service industry is currently due to increased consumer demand. In carrying out the delivery of goods by goods delivery services it does not always run smoothly, there are errors and omissions that occur, such as goods being exchanged, damaged, arriving late at the destination address causing losses to consumers. Conditions like this will be detrimental to the delivery service company. In order to compete and survive in the high demand for freight forwarding services, companies must be able to maintain and increase the productivity of their employees. Then conducted research in terms of employee productivity. The research design adapts a quantitative approach using 7 variables, namely leadership, work motivation, rewards, incentives, competence, job satisfaction and work productivity. The study used a questionnaire with an interval scale of 10 points and distributed a sample of 217 respondents, namely employees of freight forwarding services. Data analysis in this study used the SEM method with the SmartPLS 3.0 program. The results of the study clarify that leadership, incentives, job satisfaction partially have a significant effect on employee work productivity, and work motivation, rewards and competence partially have no significant effect on employee work productivity, while leadership, work motivation, and incentives indirectly through job satisfaction as an intervening variable has a positive and significant effect on employee work productivity. Meanwhile, rewards and competencies indirectly through job satisfaction as intervening variables have no significant effect on employee work productivity.